2021
DOI: 10.1093/ons/opab236
|View full text |Cite
|
Sign up to set email alerts
|

Lower Hounsfield Units at the Upper Instrumented Vertebrae are Significantly Associated With Proximal Junctional Kyphosis and Failure Near the Thoracolumbar Junction

Abstract: BACKGROUND Low bone mineral density (BMD) on dual energy x-ray absorptiometry (DXA) is likely a risk factor for proximal junctional kyphosis (PJK) and proximal junctional failure (PJF). However, prior instrumentation and degenerative changes can preclude a lumbar BMD measurement. Hounsfield units (HU) represent an alternative method to estimate BMD via targeted measurements at the intended operative levels. OBJECTIVE To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This finding is consistent with previous studies showing low bone density as a risk factor of PJF. 19,20 Based on our review, patients with a Chance-type proximal junctional fracture generally have (1) an increase in PJA (kyphosis), (2) cephalocaudal widening of the UIV pedicles, and (3) possible anterior column compression deformity of the UIV. These findings, in the setting of a patient with persistent or new pain symptoms, should prompt the surgeon to order a CT scan to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies showing low bone density as a risk factor of PJF. 19,20 Based on our review, patients with a Chance-type proximal junctional fracture generally have (1) an increase in PJA (kyphosis), (2) cephalocaudal widening of the UIV pedicles, and (3) possible anterior column compression deformity of the UIV. These findings, in the setting of a patient with persistent or new pain symptoms, should prompt the surgeon to order a CT scan to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Complications at the proximal junction of long thoracolumbar and lumbar fusion constructs are both common and burdensome to patients and health care systems 1,4. In an effort to reduce the risk of PJK and PJF, many studies have sought to identify risk factors for the development of these complications 1,5–9. In their study of patients undergoing thoracolumbar fusions that terminated proximally near the thoracolumbar junction for degenerative indications, Mikula et al 7 identified diminished HU at the UIV as a risk factor for PJK.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 In an effort to reduce the risk of PJK and PJF, many studies have sought to identify risk factors for the development of these complications. 1,[5][6][7][8][9] In their study of patients undergoing thoracolumbar fusions that terminated proximally near the thoracolumbar junction for degenerative indications, Mikula et al 7 identified diminished HU at the UIV as a risk factor for PJK. A subsequent study by the same authors revealed that lower HU at the UIV was also associated with an increased risk of PJK and PJF in patients undergoing long-construct thoracolumbar fusions that terminated proximally in the upper thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various other articles report higher PJF rates in patients with low-normal bone mineral density receiving no teriparatide treatment (range: 19%-28%). [19][20][21] To create a conservative model, we chose a PJF probability of 15% in the nonteriparatide group. Finally, of the patients who underwent revision for PJF, the probability of having a poor outcome and requiring a second reoperation was assumed to be 16% ( 10%) based on previously published studies.…”
Section: Probability Estimatesmentioning
confidence: 99%